Freiheitsgrade: Zur Differenzierung praktischer Freiheit - Stederoth, Dirk (transcript, 2015)
The discussions around the existence of human free will that have been carried out in recent years between philosophy, cognitive neuroscience, psychology and jurisprudence almost always boiled down to the bipolar answers of »yes« or »no« . Dirk Stederoth confronts this dualism with a sophisticated philosophical model of varying degrees of freedom, which at the same time takes the findings of the individual disciplines into consideration. Through this process, the gradual unfolding of the three dimensions »cognitive level« , »phases of action« and »developmental psychological levels« enables new and surprising perspectives on the central problems of freedom and responsibility.